Necessity of sustainability in architectural practices for achieving sustainable development - Sirija, M (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">The purpose of this research is to highlight the rising need of sustainable architecture for ensuring sustainability in development of present era. This paper specifies the definition of sustainable architecture and covers the need, aspects and advantages of sustainable architecture and green architecture in particular. It brings to fore the importance of sustainable architecture for development in a sustainable way. It highlights the techniques and methods by which sustainability in architecture can be achieved and adopted with its benefits to the environment as well as the society.